Fanconi anemia proteins function in mitophagy and immunity - Sumpter, Rhea (Cell, 2016)
Fanconi anemia (FA) pathway genes are important tumor suppressors whose best-characterized function is repair of damaged nuclear DNA. Herein, we describe an essential role for FA genes in two forms of selective autophagy. Genetic deletion of Fancc blocks the autophagic clearance of viruses (virophagy) and increases susceptibility to lethal viral encephalitis. FANCC interacts with Parkin; is required in vitro and in vivo for clearance of damaged mitochondria; and decreases mitochondrial ROS production and inflammasome activation. The mitophagy function of FANCC is genetically distinct from its role in genomic DNA damage repair. Moreover, additional genes in the FA pathway, including FANCA, FANCF, FANCL, FANCD2, BRCA1 and BRCA2, are required for mitophagy. Thus, members of the FA pathway represent a previously undescribed class of selective autophagy genes that function in immunity and organellar homeostasis. These findings have implications for understanding the pathogenesis of FA and cancers associated with mutations in FA genes.